2020
DOI: 10.1371/journal.pone.0235106
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 and TMPRSS2 variation in savanna monkeys (Chlorocebus spp.): Potential risk for zoonotic/anthroponotic transmission of SARS-CoV-2 and a potential model for functional studies

Abstract: The COVID-19 pandemic, caused by the coronavirus SARS-CoV-2, has devastated health infrastructure around the world. Both ACE2 (an entry receptor) and TMPRSS2 (used by the virus for spike protein priming) are key proteins to SARS-CoV-2 cell entry, enabling progression to COVID-19 in humans. Comparative genomic research into critical ACE2 binding sites, associated with the spike receptor binding domain, has suggested that African and Asian primates may also be susceptible to disease from SARS-CoV-2 infection. Sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Coronavirus entry into host cells is predominantly mediated by a spike (S) protein that forms homotrimers protruding from the viral surface [ 2 ]. The S protein of SARS-CoV-2 binds to its host receptor, angiotensin-converting enzyme 2 (ACE2), and the viral entry is subsequently primed by the protease of transmembrane serine protease 2 (TMPRSS2), another essential protein required for the fusion of the viral membrane with the host cell membrane [ 3 ]. Although the respiratory system is widely accepted as the primary organ for SARS-CoV-2 infection, recent studies have identified cells from other organs that may also be infected by SARS-CoV-2, e.g., blood vessel cells, kidney cells, brain cells, liver cells, and cardiomyocytes [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus entry into host cells is predominantly mediated by a spike (S) protein that forms homotrimers protruding from the viral surface [ 2 ]. The S protein of SARS-CoV-2 binds to its host receptor, angiotensin-converting enzyme 2 (ACE2), and the viral entry is subsequently primed by the protease of transmembrane serine protease 2 (TMPRSS2), another essential protein required for the fusion of the viral membrane with the host cell membrane [ 3 ]. Although the respiratory system is widely accepted as the primary organ for SARS-CoV-2 infection, recent studies have identified cells from other organs that may also be infected by SARS-CoV-2, e.g., blood vessel cells, kidney cells, brain cells, liver cells, and cardiomyocytes [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other species use sugars as receptors or co-receptors ( 40 ). Apart from the ACE2 receptor-binding site for virus entry, TMPRSS2 is another key protein required for viral entry into human tissue ( 45 49 ).…”
Section: Introductionmentioning
confidence: 99%
“…Now is the time for us to act and ensure that environmental protection and sustainability are included as essential components of public health initiatives and economic rebuilding (UN Sustainable Development Goals 2020). In the wake of the SARS-CoV-2 coronavirus, the world has been forced to reassess the risks that deforestation, industrial agricultural expansion, reducing the boundaries between human-wild animal contact, ecotourism, bush-meat hunting, and wet markets have on increasing zoonotic crossover events between humans and wild animals, including primates, and the kinds of mitigation procedures that must put into place to protect biodiversity (Gillespie and Leendetz 2020;Lappan et al 2020;Melin et al 2020;Schmitt et al 2020;Shan et al 2020). As primatologists, we must be part of this global discussion.…”
Section: Moving From Advocacy To Activismmentioning
confidence: 99%